MEMBANGUN KOMUNIKASI YANG EFEKTIF DENGAN GENERASI Z: PELATIHAN GURU TIK (Teknologi, Informasi dan Komunikasi) OPTIMA EDUCATION - Rut Rismanta Silalahi (LPPM UPN Veteran Jakarta, 2018)
The effectiveness of teaching and learning in the classroom is inseparable from the quality ofcommunication between the teacher and students. Differences in generations between teachers and students can create barriers to communication because each party speaks 'language' and a different style. The current generation of school students is known as generation Z. They were born in the period 1995-2010. Z generation students are very familiar with technology and the digital world. They are able to learn independently with the information they get from the internet. In class, they want an interactive learning experience and the opportunity to exchange ideas. They like to use visual communication. The characteristics of students like this are certainly a challenge for teachers who have monotonous ways of teaching, only rely on one-way lectures, and do not keep up with the times. Especially if the subjects are ICT (Technology, Information and Communication) that requires teachers to actively find out and learn the latest information technology applications. Based on this situation, the author held a communication training for ICT teachers from Optima Education. In this training, the teachers were given an understanding of the characteristics of generation Z and how to effectively communicate with them. Theoutput of this training is to increase teacher understanding to communicate with Z generation students effectively. The teachers were also asked to evaluate their previous teaching methods and make a commitment to make real changes in the teaching and learning process in the classroom.